Gestión administrativa en la Empresa Pc Soluciones de la ciudad de Babahoyo - Duarte Quintanilla, Angelica Margoth (2020)
Currently, administrative management plays a very important role within organizations whether public or private, large or small, developing a set of activities aligned to achieve the same purpose, that allows to achieve the objectives established by the organization, goes hand in hand with the fulfillment of various tasks that allow to guarantee the effectiveness of the processes in addition to preventing shortages in them. In the company Pc Solutions there is a lack in the development of activities, the control of the staff there are delays in the schedules, internal conflicts, the lack of an adequate working climate decreases the performance and generates delays in the delivery of work or maintenance or repairs, all these conflicts are generated by not applying or properly executing administrative management; the non-delegating responsibilities and lacks in communication between the manager and the collaborators generate a series of problems that triggers more difficulties of a similar nature by directly compromising the optimal development of the company and its activities.